2018
DOI: 10.29252/jrh.8.3.278
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cognitive-behavioral play therapy in the self-esteem and social anxiety of students

Abstract: Self-esteem and lack of social phobia are considered amongst the components of mental health. These features are more likely to be created during the early years of life like any other mental aspect. Hence, the present research aimed to investigate the effectiveness of cognitive-behavioral play therapy in selfesteem and social anxiety of student. The statistical population included all the students in Tehran, from whom a sample of 24 was drawn through multi-stage cluster sampling. They were randomly assigned i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Cognitive Behavioral Play Therapy (CBPT) approach has been compelling in the attachment of treatment sessions and it has explicit, tangible goals and strategies. In the previous research also stated that this therapy has increase the level ofself-esteem by 19% among students in treatment groups (Atayi, et al, 2018;Sakata, et al, 2021).…”
Section: Effects Of Cognitive Behavioral Play Therapy (Cbpt) Techniques In Control Group At Pretest and Posttest On Low Self-esteem Amongmentioning
confidence: 81%
See 2 more Smart Citations
“…Cognitive Behavioral Play Therapy (CBPT) approach has been compelling in the attachment of treatment sessions and it has explicit, tangible goals and strategies. In the previous research also stated that this therapy has increase the level ofself-esteem by 19% among students in treatment groups (Atayi, et al, 2018;Sakata, et al, 2021).…”
Section: Effects Of Cognitive Behavioral Play Therapy (Cbpt) Techniques In Control Group At Pretest and Posttest On Low Self-esteem Amongmentioning
confidence: 81%
“…In an investigation done by MadadiZavare, Kamkar and Golparvar (Ghasemian Siahkalroudi & Zarbakhsh Bahri, 2015), they demonstrated the impact of play on the expansion of self-esteem on blind students. Baggerly& Parker (Atayi, Hashemi Razini, & Hatami, 2018) concluded that group play therapy hasimpactsly affects self-esteem. Braton et al (Atayi, et al, 2018;Newman, 2020) reviewed over 82 studies and concluded that play therapy lead to the improvement of self-esteem.Based on the previous research, the study of the journal was about "Effectiveness of cognitive behavioral play therapy group on self-esteem and social skills in girls' elementary school" (2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A child's anxiety level significantly decreases when given play therapy. Reduced social anxiety is also followed by an increase in self-esteem and social skills of children who develop during the play therapy process (Atayi, Hashemi Razini, & Hatami, 2018;Mollamohammadi & Yazdkhasti, 2017). High anxiety is also found in children with academic problems such as poor academic performance and learning disabilities (Mohammadinia, Fatemi, Nasiri, & Pirnia, 2018;Stulmaker & Ray, 2015).…”
Section: Subjects Researchmentioning
confidence: 99%
“…The current study tested a direct protocol for improving self-esteem through group therapy with children, which, to the best of our knowledge, has not been adequately researched to date. Controlled studies on CBT for improving self-esteem in children have found this method to be highly effective [34,[60][61][62]. The content of CBGT designed to increase self-esteem in children focuses on identifying the thinking patterns that produce negative thoughts, on modifying thinking strategies, and on problem solving [34].…”
Section: Introductionmentioning
confidence: 99%